2020
DOI: 10.1093/ntr/ntaa208
|View full text |Cite
|
Sign up to set email alerts
|

The Cigarette Smoking Initiation and Continuation in Adolescents Undergoing a Long-Term Behavioral Intervention

Abstract: Introduction Targeting adolescents’ smoking reduces its burden on health systems. We investigated the effects of the first multidisciplinary community-based lifestyle intervention in the Eastern-Mediterranean region, on smoking initiation, continuation and risk of current smoking in Iranian adolescents. Methods The current analyses were conducted on 945 non-smoker adolescents (12-18 years) who participated in Phase II of Tehr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…14 The co-occurrence and inter-relations of parental risk factors in the family context affect children's tobacco use, and alters interventions effectiveness. 15 Although family-centered interventions have shown some effectiveness in smoking prevention in children, the evidence is not strong enough. 16 The methodological and design heterogeneity among existing interventions and behavioral programs make it difficult to draw conclusions about the best strategy, especially when maintaining the long-term effects.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…14 The co-occurrence and inter-relations of parental risk factors in the family context affect children's tobacco use, and alters interventions effectiveness. 15 Although family-centered interventions have shown some effectiveness in smoking prevention in children, the evidence is not strong enough. 16 The methodological and design heterogeneity among existing interventions and behavioral programs make it difficult to draw conclusions about the best strategy, especially when maintaining the long-term effects.…”
mentioning
confidence: 99%
“…In Iran, in particular, interventions have mostly targeted cigarette rather than other forms of tobacco use. [21][22][23][24] Our previous study in Iran 15 showed that although a multidisciplinary healthy lifestyle intervention could postpone smoking initiation and reduce the risk of becoming a current smoker in nonsmoking adolescents, it could not prevent continuation in those d Senior Researcher, (Jf˙sara@yahoo.com ), Research Center for Social Determinants of Health, Research Institute for Endocrine Sciences, Shahid Beheshti University of Medical Sciences, Tehran, Iran. e Biostatistician, (leila˙cheraghi63@yahoo.com ), Department of Epidemiology and Biostatistics, Research Institute for Endocrine Sciences, Shahid Beheshti University of Medical Sciences, Tehran, Iran.…”
mentioning
confidence: 99%
See 2 more Smart Citations